If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(-6m+2)=8+8m
We move all terms to the left:
-2(-6m+2)-(8+8m)=0
We add all the numbers together, and all the variables
-2(-6m+2)-(8m+8)=0
We multiply parentheses
12m-(8m+8)-4=0
We get rid of parentheses
12m-8m-8-4=0
We add all the numbers together, and all the variables
4m-12=0
We move all terms containing m to the left, all other terms to the right
4m=12
m=12/4
m=3
| Y=-3x^2-24x+2 | | 15=r-14 | | 3/5=6/(x+3) | | 7v-1(6-2v)=12 | | 11=r-1 | | -3(2+x)=-2(-x-2) | | |3x+1|=19 | | 7n-14=3+4n-2 | | -15+6x=1x+15 | | 3n-(n+4)=14 | | (x+7)/7=15/5 | | 4x-3=-6x+5 | | 5/1.5=m/6.75 | | (5-3x4)+49= | | 5-n=-4n+2 | | 216=1/3*36*h | | X+24-3x=12 | | Y=6x^2-12+5 | | 7/3+1/2t=3 | | 8(-2x-1=24 | | 2´x+2=16 | | X+0.5-6x=2.8x+6 | | (x+3)=(10+4)/4 | | 2´8x+2)=16 | | -10=14v14v | | (1000000-x)/500000=1,5 | | 13=b-15 | | 2(4v+6)=-(3v-1) | | 0=-5t^2+100t-10 | | 3x-2(6x-10)=-16+3(5x+4 | | 2(v-6)=37-5v | | 3x+(2x-3)=72 |